The Disappearing State and the Quasi‐Event of Immigration Control. Issue 3 (21st December 2015) - Coleman, Mat; Stuesse, Angela
Abstract: Immigration enforcement by sheriffs and police can be characterized as a proliferation of quasi‐events which never quite rise to the status of an event. This poses distinct challenges for feminist‐inspired scholarship on the state which seeks to document, ethnographically, how the state goes about its business on the ground. In this article we draw on our fieldwork experience in North Carolina and Georgia on sheriffs' and police departments' use of traffic enforcement and policing roadblocks to scrutinize drivers for their legal status, and ask how our ethnographic approach to the problem of state power inevitably stumbles in relation to the ordinariness of these practices. We conclude that feminist scholarship committed to an ethnography of the state could do much more to think through the potentially aporetic quality of that which is our common object of research—the state in practice.